Personalities and Publishing: Two Aspects of the History of the Yorkshire Archaeological Society, 1863-2013. (1st August 2013) - Barber, Brian
Abstract : This anniversary article surveys the personalities of the leading members of the society over its 150-year history and relates their changing backgrounds to wider changes in society over the period. It then describes the various publishing ventures which leading members initiated, and which form the society's permanent legacy to the history of Yorkshire.